Trypanin Disruption Affects the Motility and Infectivity of the Protozoan Trypanosoma cruzi - Saenz-Garcia, Jose L.; Borges, Beatriz S.; Souza-Melo, Normanda; Machado, Luiz V.; Miranda, Juliana S.; Pacheco-Lugo, Lisandro Alfonso; Moretti, Nilmar S.; Wheleer, Richard; Soares Medeiros, Lia C.; DaRocha, Wanderson D. (Frontiers in Cellular and Infection Microbiology, 2022)
The flagellum of Trypanosomatids is an organelle that contributes to multiple functions, including motility, cell division, and host–pathogen interaction. Trypanin was first described in Trypanosoma brucei and is part of the dynein regulatory complex. TbTrypanin knockdown parasites showed motility defects in procyclic forms; however, silencing in bloodstream forms was lethal. Since TbTrypanin mutants show drastic phenotypic changes in mammalian stages, we decided to evaluate if the Trypanosoma cruzi ortholog plays a similar role by using the CRISPR-Cas9 system to generate null mutants. A ribonucleoprotein complex of SaCas9 and sgRNA plus donor oligonucleotide were used to edit both alleles of TcTrypanin without any selectable marker. TcTrypanin −/− epimastigotes showed a lower growth rate, partially detached flagella, normal numbers of nuclei and kinetoplasts, and motility defects such as reduced displacement and speed and increased tumbling propensity. The epimastigote mutant also showed decreased efficiency of in-vitro metacyclogenesis. Mutant parasites were able to complete the entire life cycle in vitro; however, they showed a reduction in their infection capacity compared with WT and addback cultures. Our data show that T. cruzi life cycle stages have differing sensitivities to TcTrypanin deletion. In conclusion, additional work is needed to dissect the motility components of T. cruzi and to identify essential molecules for mammalian stages.